Adapting to Change: Dynamic Capabilities of K-Auto in the Transition from ICEVs to EVs in Finland - Laiho, Nora Aurora (My University, 2024)
The prevailing environmental situation and pollution caused by traffic have made many consumers question their everyday choices and created demand for more sustainable ways of traveling. Electric vehicles are now seen as the future of the automotive industry, and the Nordic countries in particular are often seen as pioneers in renewable energy and energy efficiency, as they all aim to be practically fossil-free by 2050. This study aims to analyze the current strategic position of K-Auto in the context of Finland’s shift towards electric vehicles. In addition to that, the study is investigating the internal capabilities of K-Auto in adapting to the changing market dynamic driven by the car fleet transition to electric vehicles. To better understand the challenges and opportunities that the company may face in leveraging dynamic capabilities to successfully transition from selling internal combustion engine vehicles to electric vehicles, the research is also focusing on the employee’s opinions on what the company is currently doing and what they could possibly do better. This also helps to identify the key factors influencing the development and deployment of dynamic capabilities within K-Auto to effectively respond to the shift towards electric vehicles. This study was conducted as a qualitative study with semi-structured interviews, interviewees being the employees and supervisors of K-Auto Turku. The data was collected through e-mail interviews. The data gained from the answers received was analyzed with open coding. What was found from the interviews was that many employees had a clear idea of what change management is, and five out of seven interviewees thought that the employees can contribute to the spread of EVs in Finland. Strategic position of K-Auto was described by the employees to be good and aiming to become the leading seller of EVs in Finland. K-Lataus infrastructure was mentioned multiple times as competitive advantage in the interviews, and it was also highlighted that K-Auto offers comprehensively all services related to EVs from sales, maintenance, repairs, imports, to public charging infrastructure. As opportunities for K-Auto interviewees listed expanding the collection, increasing demand in the company car market, bringing new, more affordable models to the market, extending warranty periods, investing even more in digital services, investing in private leasing pricing, and offering benefits for the customers using K-Lataus.

Vallitseva ympäristötilanne ja liikenteen aiheuttamat päästöt ovat saaneet monet kuluttajat kyseenalaistamaan arkipäivän valintojaan ja luoneet kysyntää kestävämmille matkustustavoille. Sähköajoneuvot nähdään nyt autoteollisuuden tulevaisuutena, ja etenkin Pohjoismaat nähdään usein uusiutuvan energian ja energiatehokkuuden edelläkävijöinä, sillä kaikkien Pohjoismaiden tavoitteena on olla käytännössä fossiilivapaa vuoteen 2050 mennessä. Tämän tutkimuksen tavoitteena on analysoida K-Auton nykyistä strategista asemaa Suomen siirtymessä yhä enemmän polttomoottorikäyttöistä autoista sähköautoihin. Tämän lisäksi tutkimuksessa selvitetään K-Auton sisäisiä kykyjä sopeutua muuttuvaan markkinadynamiikkaan, joka johtuu autokannan siirtymisestä sähköajoneuvoihin. Pyrkien ymmärtämään paremmin haasteita ja mahdollisuuksia, joita yritys saattaa kohdata hyödyntäessään dynaamisia kykyjä siirtyäkseen menestyksekkäästi polttomoottoriajoneuvojen myynnistä sähköajoneuvoihin, tutkimuksessa keskitytään myös työntekijöiden mielipiteisiin siitä, mitä yritys tekee tällä hetkellä ja mitä he voisivat mahdollisesti tehdä paremmin. Tämä auttaa myös tunnistamaan keskeiset tekijät, jotka vaikuttavat K-Auton dynaamisten ominaisuuksien kehittämiseen ja käyttöönottoon, jotta se voi reagoida tehokkaasti sähköautoihin siirtymiseen. Tämä tutkimus tehtiin kvalitatiivisena tutkimuksena puolistrukturoiduilla haastatteluilla, joissa haastateltavat olivat K-Auto Turun työntekijöitä ja esihenkilöitä. Tiedot kerättiin sähköpostihaastatteluilla. Saaduista vastauksista saatu data analysoitiin avoimella koodauksella. Haastatteluista selvisi, että monilla työntekijöillä oli selkeä käsitys siitä, mitä muutosjohtaminen on, ja viisi haastatellusta seitsemästä arvioi, että työntekijät voivat edistää sähköautojen leviämistä Suomessa. K-Auton strategista asemaa työntekijät kuvailivat hyväksi ja että yrityksen tavoitteena on olla Suomen johtava sähköautojen myyjä. K-Lataus-infrastruktuuri mainittiin haastatteluissa useaan otteeseen kilpailuetuna, ja korostui myös se, että K-Auto tarjoaa kattavasti kaikki sähköautoihin liittyvät palvelut myynnistä, huollosta, korjauksista, maahantuonnista julkiseen latausinfrastruktuuriin. Mahdollisuuksina K-Auton haastateltavat nostivat malliston laajentamisen, kysynnän lisäämisen työsuhdeautomarkkinoilla, uusien, edullisempien mallien tuomisen markkinoille, takuuaikojen pidentämisen, panostamisen entistä enemmän digitaalisiin palveluihin, keskittymistä yksityisen leasingin hinnoitteluun ja etujen tarjoamisen K-Latausta käyttäville asiakkaille.
Keywords: change; dynamic capabilities; electric cars; change management (leadership); competitive advantage; fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development